Упростите выражение 5-(а+3) 8-(10+в) 9-(с+7) 2+(-8+с) 3+(-d-5) 4+(а-9) 0,8-(m+3) 1,4+(n-2) 2,6-(-r+10)

Упростите выражение 5-(а+3) 8-(10+в) 9-(с+7) 2+(-8+с) 3+(-d-5) 4+(а-9) 0,8-(m+3) 1,4+(n-2) 2,6-(-r+10)
Гость
Ответ(ы) на вопрос:
Гость
№1. 1) 2x-3y-11x+8y =5у--9х 2) 5*(2a+1)-3 =10а+5-3=10а+2=2(5а+1) №2. -4*(2,5а-1,5)+5,5а-8= ( при а= минус две девятых. ) -а +6+5,5а-8=4,5а-2=4,5*(-2/9)-2=9№4 3х-(5х-(3х-1))=3х-5х-3х+1=1-5х №5 1) 5а+7b-2a-8b =3а-b 2) 2*(3a-4)+5=6а-8+5=6а-3=3(2а-1) №6 -6*(0,5х-1,5)-4,5х-8= ( при х=две третьих (дробью) -3х+9-4,5х-8=1-7,5х=1-(75/10)х= 1-(15/2)х=1-(15/2)(2/3)=1-5=-4 №7 2p-(3p-(2p-c)) =2р-3р-2р+с=с-3р №8 1) 5x+3y-2x-9y =3х-6у=3(х-2у) 2) 2*(3a-4)+5 =6а-8+5=6а-3=3(2а-1) №9 -2*(3,5у-2,5)+4,5у-1 = (при у=четыре пятых (дробью) -7у+5+4,5у-1=4-2,5у=4-(25/10)у= 4-(25/10)(4/5)=4-(5/2)(4/5)=4-2=2 №10 5а-(3а-(2а-4)) =5а-3а+2а+4=4а-4=4(а-1); №11 1) 12а-10b-10a+6b=2а-4b=2(a-2b) 2) 4*(3x-2)+7 =12х-8+7=12х-1; №12 -5*(0,6с-1,2)-1,5с-3= ( при с=минус четыре девятых. (дробью) -3с+6-1,5с-3=-4,5с+3= 3-(45/10)(2/9)=3-9/2*2/9=3-1=2 №13 7х-(5х-(3х+у)) =7х-5х+3х-у= 5х-у/2*(-2/9-2=-2.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы